Cost-Effectiveness of HRSA's Ryan White HIV/AIDS Program?. (1st February 2021) - Goyal, Ravi; Luca, Dara; Klein, Pamela W.; Morris, Eric; Mandsager, Paul; Cohen, Stacy M.; Hu, Cindy; Hotchkiss, John; Gao, Jessica; Jones, Andrew; Addison, West; O'Brien-Strain, Margaret; et al.
Abstract : Background: With an annual budget of more than $2 billion, the Health Resources and Services Administration's Ryan White HIV/AIDS Program (RWHAP) is the third largest source of public funding for HIV care and treatment in the United States, yet little analysis has been done to quantify the long-term public health and economic impacts of the federal program. Methods: Using an agent-based, stochastic model, we estimated health care costs and outcomes over a 50-year period in the presence of the RWHAP relative to those expected to prevail if the comprehensive and integrated system of medical and support services funded by the RWHAP were not available. We made a conservative assumption that, in the absence of the RWHAP, only uninsured clients would lose access to these medical and support services. Results: The model predicts that the proportion of people with HIV who are virally suppressed would be 25.2 percentage points higher in the presence of the RWHAP (82.6 percent versus 57.4 percent without the RWHAP). The number of new HIV infections would be 18 percent (190, 197) lower, the number of deaths among people with HIV would be 31 percent (267, 886) lower, the number of quality-adjusted life years would be 2.7 percent (5.6 million) higher, and the cumulative health care costs would be 25 percent ($165 billion) higher in the presence of the RWHAP relative to the counterfactual. Based on these results, the RWHAP has an incremental cost-effectiveness ratio of $29, 573 per quality-adjusted life year gained compared with the non-RWHAP scenario. Sensitivity analysis indicates that the probability of transmitting HIV via male-to-male sexual contact and the cost of antiretroviral medications have the largest effect on the cost-effectiveness of the program. Conclusions: The RWHAP would be considered very cost-effective when using standard guidelines of less than the per capita gross domestic product of the United States. The results suggest that the RWHAP plays a critical and cost-effective role in the United States' public health response to the HIV epidemic.